الدهاقين ومكانتهم الاقتصادية في الإدارة العربية الإسلامية - الدليمي، محمد حسن سهيل Aldulaimi, Mohammed Hassan Suhail (جامعة عمار ثليجي بالأغواط, 2018)
الدهاقين وهم طبقة متخصصة بالإدارة المالية في الدولة الساسانية مهمتها جمع الضرائب كونهم يتمتعون بصلاحيات رسمية كزعماء للقري ولديهم سجلات بأسماء وإعداد دافعي الضرائب من الفلاحين، وبعد تحرير العراق وفتوحات المشرق في عهد الخلافة الراشدة (13-40هـ/ 634-660م)، أدركت الحكومة الإسلامية أهمية هذه الطبقة فأبقتها في أعمال الجباية وأصبحوا المسؤولين إمام الإدارة المالية الإسلامية عن دفع الأموال المتفق عليها في المعاهدات وعهود الصلح، تمتعت هذه الطبقة باحترام وعناية الإدارة العربية الإسلامية ووفرت لها امتيازات مهمة لا سيما بعد دخولهم الإسلام بإعفائهم من دفع الجزية (ضريبة الراس) وأبقت الأراضي الزراعية تحت تصرفهم بعد دفع ضريبة الخراج وتخصيص وراتب لهم وهي امتيازات أقرها الخليفة عمر بن الخطاب وعلى بن أبي طالب رضي لله عنهم.
Al –Dahakeen are a class of financial management in the Sasanian state. Since they are a specialized layer of financial management in the Sasanian state whose task is to collect taxes because they have official powers as village leaders and have records of names and numbers of taxpayers from the farmers. After the liberation of Iraq and the conquests of the Orient in the era of the Al -Rasheda Caliphate (13 – 40 AH) where the Islamic government realized the importance of this class in the collection and became the public officials of Islamic finance management and payment of funds agreed in treaties and promises of reconciliation. This class received the patronage and respect of the Arab Islamic administration ،here it provided them with important privileges ،especially after they entered Islam ، exemption from the payment of the jizya (the head tax) and kept the agricultural lands at their disposal after paying the (Al karaj ) tax They supported by the two caliphs Omar Bin Khattab and Ali Bin Abi Taleb.
Keywords: الدهقان -- تاريخ الدهاقنة -- الدولة الساسانية -- الدولة العربية الإسلامية